2022
DOI: 10.1007/s10071-022-01698-2
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical choice and the reinforcing value of information

Abstract: Signals that reduce uncertainty can be valuable because well-informed decision-makers can better align their preferences to opportunities. However, some birds and mammals display an appetite for informative signals that cannot be used to increase returns. We explore the role that reward-predictive stimuli have in fostering such preferences, aiming at distinguishing between two putative underlying mechanisms. The ‘information hypothesis’ proposes that reducing uncertainty is reinforcing per se, somewhat consist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 82 publications
2
18
2
Order By: Relevance
“…This result suggests rats deliberate (i.e., show slowing on dual-offer trials compared to single-offer trials) and likely engage in some comparative process when deciding between options of known value. Our findings are quite different from the studies by the Kacelnik group that motivated our experiment (Fig 6 in Shapiro et al, 2008; Fig 2 in Ojeda et al, 2018; Fig 4 in Ajuwon et al, 2023). Their studies reported much longer overall response latencies (on the order of seconds).…”
Section: Discussioncontrasting
confidence: 99%
“…This result suggests rats deliberate (i.e., show slowing on dual-offer trials compared to single-offer trials) and likely engage in some comparative process when deciding between options of known value. Our findings are quite different from the studies by the Kacelnik group that motivated our experiment (Fig 6 in Shapiro et al, 2008; Fig 2 in Ojeda et al, 2018; Fig 4 in Ajuwon et al, 2023). Their studies reported much longer overall response latencies (on the order of seconds).…”
Section: Discussioncontrasting
confidence: 99%
“…One possibility concerns the effects of conditioned reinforcement. One mechanistic explanation for learned preferences for advanced information argues that subjects select the informative option because 'good news' signals anticipating forthcoming rewards acquire reinforcing properties by association with outcomes of positive valence (8,19,28,69). If any putative inhibitory effects of signals for 'bad news' in the informative option are relatively small or ignored by subjects, overall, subjects would form stronger associations between choice and reward in the informative option, but these effects may be quantitatively different between species.…”
Section: Discussionmentioning
confidence: 99%
“…In Phase 1, when presented with S-, subjects swam away from the stimulus (Figure 3;(see also 43)), and in Phase 2 subjects rarely selected S-when it was presented alongside other stimuli (Supplementary Figure 3), suggesting that stimuli for reward omission can acquire aversive properties which could inhibit Info preference. Manipulations involving the removal of S-(e.g., 19,73,74) could help to elucidate the extent to which conditioned inhibition plays a role in goldfish preferences for advanced information. Subjects in our study learnt the task contingencies, showing appropriate responses to outcome-predictive stimuli, but they did not develop a preference for informative stimuli foretelling good and bad news equally often.…”
Section: Discussionmentioning
confidence: 99%

Do goldfish like to be informed?

Ajuwon,
Monteiro,
Walton
et al. 2024
Preprint
Self Cite
“…In our information seeking task, mice move from the center port to a side port where they experience a 10s delay before receiving a water reward. We expect that were we to shorten this delay, if mice value information because it grants them access to informative cues in advance of the delayed reward, the value of information should also be reduced because it either diminished the duration of pleasurable anticipation or aversive uncertainty 6,16,19,49 . We have therefore manipulated the subjective value of information in this task by varying the length of delay on both sides, Information and no information, across blocks of sessions.…”
Section: Mice Value Informationmentioning
confidence: 99%